Analisis Penyebab Kemacetan Jalan di Pusat Kota Bandar Lampung Studi Kasus Jalan Kota Raja – Jalan Raden Intan - Nawang Sari, Yuntares Putri; Herianto, Dwi; Putra, Sasana (Universitas Lampung, 2016)
Bandar Lampung as a city that develops in many aspects, such as social,culture and economy .Especially travel on Raden Intan street, generally the most travelling occurs in the morning andaftenoon which is there are many people do activities at the same time and it makes traffic jam.The purpose of this research are determining a point of impact of traffic jam, getting a traffic jamcase and giving solution of it. Identification of traffic cases use weaving, capacity and free flowvelocity the street that was already identified. These analysis use to show connection one of partbetwwen two movement of trafficjam that converging the compare it with planned velocity in city.The results of study show that weaving, capacity and free flow velocity compare with plannedvelocity it makes decreasing of velocity on a street that was identified. Therefore, indisciplineontraffic needs a setting of row of traffic, such as a set of street row and rules of traffic fromstakeholder in this case.Keywords: a point of impact of traffic, a case of traffic jam,weaving , Capacity, free flow velocity